Perancangan Alat Peraga Visual Sekolah Minggu untuk Anak Usia Bawah Tiga Tahun di Kota Bandung - Naniwati Sulaiman (Serat Rupa: Journal of Design, 2026)
This study aims to design visual aids for Sunday School classes for toddlers. Toddlers have their own limitations in concentration and visual perception. Therefore, designing visual aids for toddlers is a challenge in itself. As a reference, Bible stories from the Suara Sekolah minggu curriculum for toddlers are used. The process of designing visual aids begins with analyzing the story material to be delivered in class, the age characteristics of toddlers, and the context of their use in the classroom by the teacher. The results of the analysis are used to determine the selection of materials and visual expression techniques used in the visual aids. The research method used is the iterative design method, a design methodology based on a cyclic process of prototyping, testing, analysis, and product refinement. Based on the results of the latest iteration of a design, changes and refinements are made. The ultimate goal of this process is to improve the quality and functionality of a design. The results of this study are expected to serve as guidelines for designing age-friendly visual aids for toddlers, as well as broaden Sunday school teachers' horizons in selecting appropriate visual aids for their students.